Implementasi Prinsip Kepentingan Terbaik Anak Dalam Pertimbangan Hakim Pada Penetapan Asal-Usul Anak Luar Nikah: Studi Putusan Nomor 33/Pdt.P/2025/PA.Smn - Khaerul Ma'arif; Ade Fita Nurani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
This study examines the implementation of the best interests of the child principle in the determination of Judges Number 33/Pdt.P/2025/PA.Smn regarding the determination of the origin of children born out of wedlock. Using a normative juridical approach, this study analyzes whether the principle of the best interests of the child is truly the main ratio decidendi in the judge's consideration, not just a complement to the juridical-formal argument. The results of the analysis show that the judge's consideration has reflected some of the indicators of this principle, including the fulfillment of the child's identity rights through the inclusion of the biological father's name in the birth certificate, the protection of children from discrimination due to the actions of their parents by citing the principles of Nemo commodum capere potest de injuria sua propria and QS. al-An'am verse 164, the use of the maqashid al-shari'ah framework, especially hifzh al-nasl, as well as the reference to the Constitutional Court Decision Number 46/PUU-VIII/2010. However, the judge's consideration is still partial because it does not touch the dimensions of children's participation rights, assessment of parental parenting capacity, the psychosocial impact of children, and the implications of inheritance rights from the determination of fate, so that it has not made the best interests of the child a primary consideration that stands alone methodologically. This research contributes to the development of a more holistic standard of judicial consideration in cases of determining the origin of children in the Religious Courts.